Transient stripping of subducting slabs controls periodic forearc uplift - Armel Menant (Nature Portfolio, 2020)
Topography at active forearc margins is controlled by numerous competing tectonic and erosional processes acting at different timescales, yet separating their respective contribution remains a challenge. Here, the authors evidence Myr-scale, uplift-then-subsidence cycles controlled by transient accretion at the base of the forearc domain.